Vaginal rejuvenation using energy-based devices - Cheryl Karcher, MD; Neil Sadick, MD (Wolters Kluwer, 2016)
Physiologic changes in a woman's life, such as childbirth, weight fluctuations, and hormonal changes due to aging and menopause, may alter the laxity of the vaginal canal, damage the pelvic floor, and devitalize the mucosal tone of the vaginal wall. These events often lead to the development of genitourinary conditions such as stress urinary incontinence; vaginal atrophy; dryness; and physiologic distress affecting a woman's quality of life, self-confidence, and sexuality. Various treatment modalities are currently available to manage these indications, varying from invasive vaginal surgery to more benign treatments like topical vaginal hormonal gels or hormone-replacement therapy. A new trend gaining momentum is the advent of energy-based devices for vaginal rejuvenation that apply thermal or nonthermal energy to the various layers of the vaginal tissue, stimulating collagen regeneration contracture of elastin fibers, neovascularization, and improved vaginal lubrication. This review aims to present the available technologies offering vaginal rejuvenation and the scientific evidence that underlines their safety and efficacy for this indication.